THE FUNCTION OF SLANG WORDS FOUND IN THE AFTER PARTY MOVIE DIRECTED BY IAN EDELMAN - Mahendro Adji Lelono; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This research aims to identify the function of slang words found in The After Party movie directed by Ian Edelman. This research focuses on classifying the function of slang words found in the movie by using the theory of function of slang words proposed by Zhou & Fan (2013). Descriptive qualitative approach was utilized in this research and the data was collected from the movie and the subtitles. The researcher collected the data through watching the movie, reading its subtitles, determining slang words, making notes, and classifying the data. In analyzing data, the researcher implemented interactive model analysis which consisted of four stages of analyzing data; data collection, data reduction, data presentation, and conclusion. The researcher found 85 slang terms uttered by characters from the movie. The characters utilized 12 slang terms to pursuit self-identity as part of particular groups, 52 slang terms to show emotive feelings of the users, and 21 slang terms to achieve politeness in maintaining relationship with others. Key words: Slang, Function, The After Party Movie